Distribution of trace metals and rare earth elements in rocky shore organisms along the east coast of Peninsular Malaysia - Mohd Fuad Miskon (Institut Oseanografi, 2012)
Interspecies, inter-tissue and interspatial variations of trace metals and rare earth elements (REEs) in selected body parts of Saccostrea cucullata, Thais clavigera and Nerita chameleon along the east coast of Peninsular Malaysia were determined. Significant interspatial variations (p<0.05 and p<0.01) in trace metals and REEs were recorded.